THE EFFECTS OF ART THERAPY ACTIVITIES SETS FOR CONCENTRATION DEVELOPMENT OF AUTISM CHILDRENS IN A LEANING’S CENTER IN ANGTHONG PROVINCE - Kullananthitichoti, Nanthalida; Aphipanyo, Phrapalad Soravit; Woramongkhalo, Phrakhrupalad Marut; Mererk, Sayyud; Vachirapanyo, Phrasamu Chokdee; Khammawaro (Siriyan), Phra Winai (Journal of Educational Review Faculty of Education in MCU, 2024)
The objectives of this research article ware 1) to create a set of art therapy activities that have an effect on the development of concentration of autistic children in a learning center in Ang Thong Province and 2) the effect of a set of art therapy activities on the development of concentration of children with autism in a learning center in Ang Thong Province. This was a quasi-experimental research with a single subject design, A-B-A-B format, with 4 phases, collecting data from attention behavior of 2 autistic children as a sample group, treatment was given one person at a different time to obtain the effect of art therapy activity sets on the development of concentration of autistic children. Analyzing data by finding basic statistics such as frequencies, averages, and present data analysis results with tables and line graphs (Visual Analysis) and then wrote a research report using descriptive analysis. The results of the study found that creating a set of art therapy activities that affect children's concentration development Autism in a learning center in Ang Thong Province developed this time; 1 set consisting of 6 activities: Drawing and painting activities, watercolor printing activities from natural materials, cutting and pasting activities to build relationships, activities to practice creativity with sculpture, hanging picture of large family activities, and activities to create pictures with paper mache. The activity sets were arranged in order from basic art activities; easy to difficult with increasing effort, time, and concentration in making art. It directly affected the development of concentration. Effects of art therapy activity sets on the concentration development of autistic children in a learning center in Ang Thong Province after using the art therapy activity kit, children with autism developed concentration differently than before using the activity kit. Both autistic children who received behavioral adjustments with art therapy activity sets had better concentration behavior. The first child, when behavior adjustments were received, concentration behavior improved from the average baseline period by as much as 43.91 percent, while the second child's concentration improved from the baseline by an average of 29.64 percent, showing that the art therapy activity set had an effect on the development of concentration of autistic children and be able to maintain concentration. After using the art therapy activity kit, both autistic children had a different development in concentration than before using the activity kit; =15.35 (after), =24.15 (before), the rate of reduction was down to 36.44 percent.